Results of endoscopic surgery and intralesional steroid therapy for airway compromise due to tracheobronchial Wegener's granulomatosis. Issue 1 (15th June 2007) - Nouraei, S A R; Obholzer, R; Ind, P W; Salama, A D; Pusey, C D; Porter, F; Howard, D J; Sandhu, G S
Abstract : Background: Upper airway compromise due to tracheobronchial stenosis commonly occurs in patients with Wegener's granulomatosis (WG). There is at present no consensus on the optimal management of this life threatening condition. Objective: To assess the results of laryngo-tracheo-bronchoscopy, intralesional steroid therapy, laser surgery and dilatation in managing obstructive tracheobronchial WG. Methods: Records of 18 previously untreated stridulous patients with obstructive tracheobronchial WG, treated between 2004 and 2006, were prospectively recorded on an airway database and retrospectively reviewed. Information about patient and lesion characteristics and treatment details were recorded. Treatment progress was illustrated using a timeline plot, and intervention-free intervals were calculated with actuarial analysis. Results: There were nine males and the average age at presentation was 40 (16) years (range 13–74). There were 13 patients with tracheal and five with tracheal and bronchial lesions. The average tracheal lesion height was 8 (3) mm, located 23 (9) mm below the glottis. There were 1, 10 and 7 Myer-Cotton grade I, II and III lesions, respectively. Mean intervention-free interval following minimally invasive treatment was 26 (2.8) months. Following endobronchial therapy, the median intervention-free interval was 22 months (p>0.8 vs tracheal lesions). No patient required a tracheostomy or endoluminal stenting. Conclusions: Intralesional steroid therapy and conservative endoluminal surgery is an effective strategy for treating airway compromise due to active tracheal and bronchial WG, obviating the need for airway bypass or stenting. We recommend the combination of endotracheal dilatation, conservative laser surgery and steroid therapy as the standard of care for treating airway compromise due to obstructive tracheobronchial WG.